Penerapan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM) pada Laporan Keuangan Usaha Mikro, Kecil, dan Menengah (UMKM) Filemon Phone di Pontianak - Leli, Leli (Jurnal KIAFE, 2024)
This study examines the application of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in the preparation of financial statements at Filemon Phone, a micro, small, and medium enterprise in Pontianak. The study employs a qualitative case study approach. Data were collected through interviews, observations, literature review, and documentation. The results show that Filemon Phone had not prepared financial statements in accordance with SAK EMKM and only recorded revenues and expenses in a simple manner. Based on the available data, the study prepared a statement of financial position, an income statement, and notes to the financial statements for the period from January to March 2023. The findings indicate that SAK EMKM can be applied to Filemon Phone. However, its implementation is constrained by the owner’s limited accounting knowledge, the absence of employees capable of preparing financial statements, limited time to learn accounting, a lack of government outreach, and the absence of external demand for formal financial reports. Applying SAK EMKM can help the business evaluate its performance, control operating costs, support decision-making, and improve access to external financing.